Selection and Characterization of Burkholderia spp. for Their Plant-Growth Promoting Effects and Influence on Maize Seed Germination - dos Santos, Isaneli Batista; Pereira, Arthur Prudêncio de Araújo; de Souza, Adijailton José; Cardoso, Elke Jurandy Bran Nogueira; da Silva, Flaviana Gonçalves; Oliveira, João Tiago Correia; Verdi, Maria Carolina Quecine; Sobral, Júlia Kuklinsky (Frontiers in Soil Science, 2022)
Burkholderia sp. is a bacterial genus extremely versatile in the environment and has been reported for a great potential to promote plant growth via different mechanisms. Here we evaluate the plant growth-promoting mechanisms in twenty-six Burkholderia strains. Strains were evaluated for their ability to promote plant growth by means of: indole-3-acetic acid (IAA) production under different conditions of pH, salt stress and the presence or absence of L-tryptophan; exopolysaccharides (EPS) production and quorum sensing (ALH). The strains were also characterized in terms of their genetic variability and species identification through Sanger sequencing. Then, the bacteria most responsive in the greatest number of plant-growth promotion mechanisms were selected for a corn seed germination test. All bacteria synthesized IAA in medium with 0.0 or 5.0 mM of L-tryptophan in combination with either 1% or 5% of NaCl, and pH values of either 4.5 or 7.2. The EPS production was confirmed for 61.54% of the bacterial strains. Quorum sensing also occurred in 92.3% of the selected bacteria. The Jaccard similarity coefficient revealed 16 clusters with high genetic variability between bacterial strains. Bacterial strains were assigned to seven species: B. anthina, B. cepacia , B. gladioli, B. ambifaria, B. graminis, B. heleia, and Burkholderia spp. The corn seed bacterization did not affect the germination velocity index (GSI), as well as the first count of germinated seeds (FC). However, inoculations formulated with B. heleia strain G28, B. gladioli strain UAGC723, and B. graminis strain UAGC348 promoted significant increases in root length, seedling height and fresh and dry seedling phytomass, respectively. These results indicate the high biotechnological potential of several strains in the genus Burkholderia sp. as seed inoculants, favoring germination and seedling initial development.